2018
DOI: 10.1007/s11274-018-2417-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial composition and diversity in a long-term petroleum contaminated soil and isolation of high-efficiency alkane-degrading strains using an improved medium

Abstract: Bacterial community and diversity in a long-term petroleum-contaminated soil of an oilfield were characterized using 16S rRNA gene-based Illumina MiSeq high-throughput sequencing. Results indicated that Proteobacteria (49.11%) and Actinobacteria (24.24%) were the most dominant phyla, and the most abundant genera were Pseudoxanthomonas (8.47%), Luteimonas (3.64%), Alkanindiges (9.76%), Acinetobacter (5.26%) and Agromyces (8.56%) in the soil. Meanwhile a series of cultivations were carried out for isolation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…In group C, the genus Ochrobactrum increased from 0Á94 to 15Á37%, Flavobacterium increased from 0Á20 to 11Á09%. Flavobacterium and Ochrobactrum have been reported to effectively degrade polycyclic aromatic hydrocarbons such as alkanes, benzene, toluene, ethylbenzene, xylene, phenanthrene and benzopyrene (Zheng et al 2018). The same results were also found by Ding and Yokota (2010), who reported that the Rpf from M. luteus resuscitated the Gram-positive bacteria, and promoted the growth of several Gram-negative bacteria, such as Curvibacter fontana.…”
Section: Resultssupporting
confidence: 62%
“…In group C, the genus Ochrobactrum increased from 0Á94 to 15Á37%, Flavobacterium increased from 0Á20 to 11Á09%. Flavobacterium and Ochrobactrum have been reported to effectively degrade polycyclic aromatic hydrocarbons such as alkanes, benzene, toluene, ethylbenzene, xylene, phenanthrene and benzopyrene (Zheng et al 2018). The same results were also found by Ding and Yokota (2010), who reported that the Rpf from M. luteus resuscitated the Gram-positive bacteria, and promoted the growth of several Gram-negative bacteria, such as Curvibacter fontana.…”
Section: Resultssupporting
confidence: 62%
“…Sufficient time is needed to synthesize hydrocarbon-degrading enzymes because of the requirements of bacterial growth and synthetic metabolism. Although some bacteria have been reported to mineralize petroleum hydrocarbons completely within several days, or even less than 1 day under culture conditions, the degradation efficiency of these bacteria makes it difficult to meet the expected effects in practical usage (Chen et al, 2017; Zheng et al, 2018). The complex combination of various biological and abiotic factors limits the function of petroleum hydrocarbon-degrading bacteria in many ways (Zhao et al, 2017; Wang Y. et al, 2018).…”
Section: Time Consumingmentioning
confidence: 99%
“…We demonstrated that the separate sterilization of agar and phosphate (termed the "PS" protocol, where "S" indicates "separate") minimized ROS generation, which improved the culturability of environmental microorganisms. The PS protocol has been shown to improve the culturability of a wide range of microorganisms, including slow-growing heterotrophs (Kato et al, 2018), hard-to-culture Actinobacteria (Adam et al, 2018), and alkane-degrading bacteria (Zheng et al, 2018). Furthermore, many research groups reported the isolation of novel bacterial taxa using the PS protocol (Nishioka et al, 2016;Huang et al, 2017;Kitzinger et al, 2018;Rilling et al, 2018).…”
mentioning
confidence: 99%